Economic Value of Herbicide Programs and Implications for Resistance Management in North Carolina. Issue 1 (1st July 2014) - Jordan, David; York, Alan; Seagroves, Rick; Everman, Wesley; Clewis, Bart; Wilcut, John; Shaw, David; Owen, Michael; Wilson, Robert; Young, Bryan; Weller, Stephen
Abstract : Farm‐scale experiments were conducted in North Carolina during 2006–2009 in continuous cotton ( Gossypium hirsutum L.), continuous soybean [ Glycine max (L.) Merr.], and corn ( Zea mays L.)–soybean rotation crop systems to compare growers' standard weed management practice (SP) with best management practice (BMP) recommended by university weed scientists to delay or prevent the evolution of herbicide‐resistant weeds. The BMP included a greater diversity of herbicides and number of herbicide applications over the 4 years of the experiment. For the continuous cotton–soybean crop systems, increases in herbicide cost, crop yield, and economic return were noted with the BMP compared with the SP. Soybean yields increased with the BMP in the corn–soybean rotation. However, corn yield and economic return of the rotation did not increase with the BMP. The diversity of herbicide active ingredients, often reflecting diversity of herbicide modes of action (MOA), increased with the BMP. Weed population density was lower with the BMP before postemergence (POST) herbicide application for continuous cotton and soybean but did not differ for the corn–soybean rotation. These data suggest that the more intensive and herbicide‐diverse BMP was at least as cost effective as the lower‐priced SP. The economic benefits of the BMP increased as crop price increased.